2-(Arylamino)aryliminophosphoranes as Easily Available and Convenient Starting Materials in the Synthesis of 1,2,3-Benzotriazoles - Łukasik, Emilia; Wróbel, Zbigniew (Synlett, 2014)
1-Aryl-1,2,3-benzotriazole systems are synthesized in the high-yielding cyclocondensation of 2-(arylamino)aryliminophosphoranes under mild conditions. The reaction concludes the three-step, halogen-free synthetic route starting from simple nitroarenes and arylamines.
Keywords: cyclization; condensation; heterocycles; annulation; ylides